Recent Research Analysis in Acupotomy - Ji Hoon Han; Hyang Gi Lim; Jae Hyung Kim; Eun Sil Heo; Ga-Young Choi; Seong Hun Choi; Sang Ha Woo; Jung Hee Lee; Yun Kyu Lee; Jae Soo Kim; Hyun-Jong Lee (MEDrang Inc., 2023)
Between May 2014 and April 2022, a total of 926 articles were retrieved from the international database, and a total of 233 articles were retrieved from the Korean database. From there, 14 studies were selected, and evaluated by the published year, terminology of the acupotomy, sample size, disease type, retention time, treatment sites, insertion depth and size of the acupotomy, treatment frequency, and duration, type of acupotomy manipulation method, evaluation index, therapeutic effects, adverse effects, and assessment of the risk of bias in randomized controlled trials. This study examined the need for additional acupotomy studies to secure an objective basis for the application of clinical treatment. Furthermore, the detailed description of the study methods and results and unified terminology can provide evidence for the efficacy of acupotomy.